Induction of Resistance in Citrus reticulata against Fusarium solani by Dual Application of AMF and Trichoderma asperellum - Allay, S.; Chakraborty, B. N. (International Journal of Bio-resource and Stress Management, 2023)
Decline of health status of nursery grown saplings of Citrus reticulata due to root rot caused by Fusarium solani is increasingly posing a major threat to the farmers of Darjeeling hill. One of the potential biocontrol fungus-Trichoderma asperellum isolated from mandarin rhizosphere, showing in vitro antagonistic reaction against the root rot pathogen-F. solani as well as showing plant growth promotion has been selected for application following root inoculation with Glomus fasciculatum and Gigaspora gigantea, dominant arbuscular mycorrhizal fungi (AMF) associated with mandarin roots. 18S rDNA sequence based molecular detection of F. solani and T. asperellum was done. PAbs separately raised against F. solani, T. asperellum, G. fasciculatum and Gi. gigantea, were purified and packaged into serological formats such as PTA-ELISA, DIBA, western blot and immunofluorescence. Successful root colonization with G. fasciculatum and Gi. gigantea was confirmed by their cellular localization in mandarin root tissues following FITC labeled immunofluorescence assay. Enhanced growth of the saplings in AMF inoculated plants was evident as compared with untreated healthy plants. Application of G. fasciculatum, Gi. gigantea and T. asperellum singly or jointly suppressed root rot of mandarin. Induction of major defense enzymes such as chitinase, β, 1-3 glucanase and peroxidase by treatment with AMF and T. asperellum was evident. One induced isoform of peroxizymes following AMF inoculation as well as application of T. asperellum was confirmed in PAGE analyses. Concomitant increase in defense enzymes following inoculation with F. solani was correlated with the induction of resistance in mandarin plants using bioinoculants.